Scientific activities responsible for successful forest greening in Korea. Issue 1 (2nd January 2017) - Park, Hyun; Lee, Jee Yeun; Song, Minkyung
ABSTRACT: Successful forest greening aligned with economic growth implemented by Korea is considered best practice in most developing countries. However, the specific technologies used for this greening process in Korea have been insufficiently described. In this study we extensively reviewed papers published in academic journals and related documents regarding greening projects. We identified significant contributions from five technological areas related to forest greening in accordance with policies: (1) forest survey and inventory; (2) tree improvement; (3) seeds and nurseries; (4) tree planting and tendering; and (5) forest pest control. In conclusion, the forest greening of Korea has been successfully achieved through a combination of investment in forest protection with a well-equipped technological base that has helped us select suitable species, prepare seedlings, and plant and nurture the trees properly. Meanwhile, we also found that official development assistance (ODA) from the international community contributed significantly to the greening activities of Korea to overcome technical and economic limitations. Thus, based on the successful example of forest greening in Korea, to restore degraded forests in developing countries a systemized ODA should be provided to support the development of a scientific and technological base for developing countries.